The bony labyrinth in the Aroeira 3 Middle Pleistocene cranium. Issue 124 (November 2018) - Conde-Valverde, Mercedes; Quam, Rolf; Martínez, Ignacio; Arsuaga, Juan-Luis; Daura, Joan; Sanz, Montserrat; Zilhão, João
Abstract: The discovery of a partial cranium at the site of Aroeira (Portugal) dating to 389–436 ka augments the current sample of Middle Pleistocene European crania and makes this specimen penecontemporaneous with the fossils from the geographically close Atapuerca Sima de los Huesos (SH) and Arago sites. A recent study of the cranium documented a unique combination of primitive and derived features. The Aroeira 3 cranium preserves the right temporal bone, including the petrosal portion. Virtual reconstruction of the bony labyrinth from μCT scans provides an opportunity to examine its morphology. A series of standard linear and angular measures of the semicircular canals and cochlea in Aroeira 3 were compared with other fossil hominins and recent humans. Our analysis has revealed the absence of derived Neandertal features in Aroeira 3. In particular, the specimen lacks both the derived canal proportions and the low position of the posterior canal, two of the most diagnostic features of the Neandertal bony labyrinth, and Aroeira 3 is more primitive in these features than the Atapuerca (SH) sample. One potentially derived feature (low shape index of the cochlear basal turn) is shared between Aroeira 3 and the Atapuerca (SH) hominins, but is absent in Neandertals. The results of our study provide new insights into Middle Pleistocene population dynamics close to the origin of the Neandertal clade. In particular, the contrasting inner ear morphology between Aroeira 3 and the Atapuerca (SH) hominins suggests a degree of demographic isolation, despite the close geographic proximity and similar age of these two sites.